Memory of the Capixaba Seminar on Art Teaching - Rebouças , Moema Martins (Farol, 2024)
The article is dedicated to reliving the memory of an event that took place 30 years ago. But how can I give existence to this memory, which I have imprinted on myself, with that of the event itself? I searched for material stored in a personal archive made up of printed materials in order to combine it with other digital and publicly accessible archives. Finally, I invited short testimonies about the significance of the seminars in their personal and professional lives from those who were the main presence and reason for the event - primary school teachers.